Implementasi Rational Emotive Behavior Therapy pada Orangtua dalam Mendampingi Anak Belajar Masa Covid-19 - Pebriyanti, Sela (Program Studi Pendidikan Islam Anak Usia Dini, Fakultas Ilmu Tarbiyah dan Keguruan, UIN Sunan Kalijaga, Yogyakarta, 2020)
Currently Indonesia is struggling against Covid-19, in anticipation of the spread of more governments, implementing various efforts, one of which is related to the learning system that is usually carried out in campus schools or other educational institutions. Now the learning is temporarily at home or at home learning this is of course the role of parents in assisting children's learning is needed. but sometimes especially mothers are often confused in allocating time to always accompany the child to learn, especially he must take care of family needs so that it is not uncommon for the response shown to children to be less good. This research focuses on the response of a housewife in assisting the learning of children in the co-19 period. The approach used in this study is rational emotive behavior therapy. In the research process researchers used descriptive qualitative methods. the purpose of this study is to be able to know the implementation of REBT towards parents in assisting the learning of children in the co-19 period. The results showed that the use of REBT when implemented sufficiently made changes to the behavior and rationality or mindset in assisting children's learning.